Toward a new generation of vaccines: The anti-cytokine therapeutic vaccines - Zagury, Daniel (The National Academy of Sciences, 2001)
Pathological conditions, such as cancers, viral infections, and autoimmune diseases, are associated with abnormal cytokine production, and the morbidity associated with many medical disorders is often directly a result of cytokine production. Because of the absence of negative feedback control occurring in some pathophysiologic situations, a given cytokine may flood and accumulate in the extracellular compartment of tissues or tumors thereby impairing the cytokine network homeostasis and contributing to local pathogenesis. To evaluate whether the rise of anti-cytokine Abs by vaccination is an effective way to treat these pathological conditions without being harmful to the organism, we have analyzed each step of the cytokine process (involving cytokine production, target response, and feedback regulation) and have considered them in the local context of effector–target cell microenvironment and in the overall context of the macroenvironment of the immune system of the organism. In pathologic tissues, Abs of high affinity, as raised by anti-cytokine vaccination, should neutralize the pool of cytokines ectopically accumulated in the extracellular compartment, thus counteracting their pathogenic effects. In contrast, the same Abs should not interfere with cytokine processes occurring in normal tissues, because under physiologic conditions cytokine production by effector cells (induced by activation but controlled by negative feedback regulation) does not accumulate in the extracellular compartment. These concepts are consistent with results showing that following animal and human anti-cytokine vaccination, induction of high-affinity Abs has proven to be safe and effective and encourages this approach as a pioneering avenue of therapy.